Vitiligo associated with ribociclib therapy: a rare case report - Wang, Zirui; Bai, Yuanrui; Wu, Rihan; Liu, Yihui; Dong, Chunhui; Chen, Ling (Frontiers in Oncology, 2025)
BackgroundRibociclib, a cyclin-dependent kinase 4/6 (CDK4/6) inhibitor, occupies a pivotal role in the clinical management of metastatic breast cancer, with its hematologic and gastrointestinal toxicities well-established. However, cutaneous adverse reactions induced by this agent—among which vitiligo is particularly prominent—are extremely rare. Herein, we report a case of vitiligo-like lesions induced by ribociclib, aiming to elucidate this underrecognized drug-adverse reaction association and conduct an in-depth analysis of its potential immune-mediated mechanism.Case summaryA 59-year-old woman with ER/PR (90% strong+), HER2-negative metastatic breast cancer developed pruritic hypopigmented patches on her forearms 16 months after initiating ribociclib/letrozole. Dermoscopy revealed complete pigment loss, peripheral hyperpigmentation, and telangiectasia. Wood’s lamp examination demonstrated bright blue-white fluorescence, confirming non-segmental vitiligo. No personal/family history of autoimmunity was noted. Topical 0.1% mometasone cream and 0.1% tacrolimus ointment were initiated, with stabilization of existing lesions and no new depigmentation at 2-month follow-up. Ribociclib was maintained due to ongoing tumor control.ConclusionsHR-positive metastatic breast cancer patients using ribociclib may develop vitiligo, with individual differences (e.g., over one-year incubation as in this case). Combined with prior reports, it suggests a link between ribociclib and vitiligo. Further clinical observations and studies are needed to confirm causality, and pre-use risk explanations to patients are advisable.